Multiple neurocysticercosis (more than 400 lesions) with intraventricular involvement - Dhananjaya, Krishnappa; Kiran, Srinivas; Gowda, Yallappa (Journal of Pediatric Neurology, 2011)
Neurocysticercosis (NCC) is the most common central nervous system parasitic disease worldwide, but cysticercal meningitis and intraventricular lesions are relatively rare, especially in Indian patients. Disseminated NCC with numerous cysts may give rise to the so-called "starry-sky" appearance on neuroimaging studies. Magnetic resonance imaging allows optimal identification of scolex and visualization of extraparenchymal cysts. We herein report a girl with multiple NCC (more than 400 lesions) with intraventricular involvement, but without focal neurological deficit on examination.
Keywords: Multiple neurocysticercosis; intraventricular cyst; "starry-sky" appearance